Definite familial multiple system atrophy with unknown genetics. Issue 3 (7th January 2014) - Itoh, Kyoko; Kasai, Takashi; Tsuji, Yukiko; Saito, Kozo; Mizuta, Ikuko; Harada, Yoshinori; Sudoh, Shinji; Mizuno, Toshiki; Nakagawa, Masanori; Fushiki, Shinji
<x xml:space="preserve">Abstract</x> Multiple system atrophy (MSA) is an oligodendrogliopathy of presumably sporadic origin, characterized by prominent α‐synuclein inclusions with neuronal multisystem degeneration, although a few Mendelian pedigrees have been reported. Here we report two familial cases of MSA of unknown genetic background. One patient was diagnosed as a possible MSA‐C (cerebellar dysfuntion) case, and the other as clinically possible MSA‐P (parkinsonism), which turned out to be definite MSA, based on a detailed autopsy. The neuropathology showed extensive deposition of α‐synuclein in the glia as well as in the neurons located in the cerebral cortices and hippocampal systems, although neither multiplication of the SNCA gene or mutations in COQ2 gene were identified in the family concerned.